Identification of target genes for spermatogenic cell-specific KRAB transcription factor ZFP819 in a male germ cell line. Issue 1 (December 2017) - Jin, Sora; Choi, Heejin; Kwon, Jun; Kim, Jihye; Jeong, Juri; Kim, Jaehwan; Hong, Seong; Cho, Chunghee
Abstract Background Zfp819, a member of theKrüppel -associated box (KRAB) family, encodes a spermatogenic cell-specific transcription factor.Zfp819 -overexpression induces apoptosis and inhibits proliferation in somatic cell lines. Results In the present study, we examined the cellular effects ofZfp819 in a male germ cell line (GC-2 cells). Overexpression ofZfp819 demonstrated an increase in the number of apoptotic cells, leading to inhibition of proliferation in GC-2 cells. We further investigated genes regulated by ZFP819 using microarray analysis and chromatin-immunoprecipitation combined with microarray analysis (ChIP-chip) in GC-2 cells. We identified 118 downregulated genes inZfp819 -overexpressing GC-2 cells using microarray analysis. ChIP-chip assay revealed that 1011 promoter sites (corresponding to 262 genes) were specifically enriched in GC-2 cells transfected withZfp819 . Two genes (trinucleotide repeat containing 6b and annexin A11) were commonly found when we compared the data between microarray and ChIP-chip analyses. Consistent with these results, Zfp819 overexpression significantly reduced the transcript levels of the two genes by binding to their promoter regions. Tissue distribution analysis indicated that both genes were predominantly expressed in testis. It has been reported that these two genes function in apoptosis. Conclusion Collectively, our study provides inclusive information on germ cell-specific gene regulation by ZFP819, which is involved in apoptosis, to maintain the integrity of spermatogenesis.